Investigating the Effect of Zinc Salts on Escherichia coli and Enterococcus faecalis Biofilm Formation - Sara Deumić; Ahmed El Sayed; Mahmoud Hsino; Andrzej Kulesa; Neira Crnčević; Naida Vladavić; Aja Borić; Monia Avdić (Applied Sciences)
Water supply and sewage drainage pipes have a critical role to play in the provision of clean water and sanitation, and pipe material selection influences infrastructure life, water quality, and microbial communities. Zinc-containing compounds are highly valued due to their mechanical properties, anticorrosion behavior, and antimicrobial properties. However, the effect of zinc salts, such as zinc sulfate heptahydrate and zinc chloride, on biofilm-forming bacteria, including Escherichia coli and Enterococcus faecalis, is not well established. This study investigates the antibacterial properties of these zinc salts under simulated pipeline conditions using minimum inhibitory concentration assays, biofilm production assays, and antibiotic sensitivity tests. Findings indicate that zinc chloride is more antimicrobial due to its higher solubility and bioavailability of Zn2+ ions. At higher concentrations, zinc salts inhibit the development of a biofilm, whereas sub-inhibitory concentrations enhance the growth of biofilm, suggesting a stress response in bacteria. zinc chloride also enhances antibiotic efficacy against E. coli but induces resistance in E. faecalis. These findings highlight the dual role of zinc salts in preventing biofilm formation and modulating antimicrobial resistance, necessitating further research to optimize material selection for water distribution networks and mitigate biofilm-associated risks in pipeline systems.